The Ilima-Letsema programme's contribution to poverty alleviation in Gauteng Province, South Africa - Nkgudi, Tshidi Mokgadi; Maake, Matome Moshobane Simeon; Masekoameng, Mosima Rachel (Frontiers in Sustainable Food Systems, 2022)
The South African government initiated the Ilima-Letsema programme to promote sustainable agricultural activities and improve the livelihoods of households in farming communities. The purpose of the paper is to evaluate the Ilima-Letsema programme's contribution to job creation and poverty alleviation in the Midvaal Local Municipality of Gauteng Province, South Africa. The quantitative research approach and survey design were used to conduct the study. Data were collected from 196 beneficiaries of the programme through face-to-face interviews using structured questionnaires. Primary data were analyzed using descriptive statistics, T-test, Multiple Linear Regression (MLR), Correlation, Cochran's Q and McNemar tests. The results indicated that the Ilima-Letsema programme significantly increased farmers' income and created jobs. Net farm income was positively and significantly influenced by education level, farmland size and jobs created. Net farm income was a significant predictor of jobs created in the post-support era, whereas education level and farmland size had negative impact. In addition, the programme significantly uplifted the elite beneficiaries from the upper-bound poverty line (UPBL); however, it did not uplift poor farmers from the food poverty line (FPL) and lower bound poverty line (LBPL). Education, farmland size and income had a positive and significant correlation (p < 0.05) with the programme's ability to uplift the beneficiaries from FPL, UBPL and UPBL amounts. It is recommended that Ilima-Letsema's rollout and budget should be expanded to enable more farmers to generate income and create employment opportunities for unskilled laborers in the agricultural sector. Again, the criteria for the programme should be changed in favor of less educated and resource-poor smallholder farmers, and producers with low net income.